THE INFLUENCE OF MANAGEMENT INFORMATION SYSTEM (SIM) TOWARD APARATUR PERFORMANCE AND INSTITUTIONAL INSTITUTIONS OF KUALA VILLAGE, KILAN SUB-DISTRICT, BATANG CENAKU DISTRICT, INDRAGIRI HULU DISTRICTS - Abdul Hairudin; Walmi Sholihat (JURNAL MANAJEMEN DAN BISNIS, 2020)
This research was conducted in the village of Kuala Kilan, Batang Cenaku District - Indragiri Hulu Regency. The type of data used in this study is primary data obtained from the recapitulation of questionnaires from the Village Apparatus and Community Institutions of Kuala Kilan Village. The analysis that I use is Simple Regression Analysis using SPSS (statistical package for social sciences) version 21 to get the output to conclude the results of this study. The results of the study concluded that the Management Information System (SIM) affected the Performance of Apparatus and Social Institutions in Kuala Kilan Village, Batang Cenaku Subdistrict, Indragiri Hulu Regency, it can be seen that the calculated t value was greater than t table (4,875> 2,03951). Based on data testing criteria, it can be seen that H0 is rejected and Ha is accepted, meaning that the Management Information System (SIM) partially influences the Performance of Apparatus and Community Institutions.